UKURAN PERUSAHAAN SEBAGAI PEMODERASI PEMBIAYAAN MURABAHAH, MUDHARABAH DAN MUSYARAKAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Sarno Sarno (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2020)
This study aims to determine the ability of company size in moderating the effect of murabahah, mudharabah and musyarakah financing on profitability (Return on assets) of Islamic Commercial Banks for the 2015-2018 period. This research data in the form of panel data obtained from quarterly financial statements of Islamic Commercial Banks then processed with Eviews 9. The results show partially murabahah financing does not affect profitability, while mudharabah and musyarakah financing have a significant effect. Simultaneously, murabahah, mudharabah and musyarakah financing have an effect on profitability. As a moderating variable, firm size weakens the effect of mudharabah financing on profitability, while on the influence of murabahah and musyarakah financing, firm size does not provide a moderating effect. This does not mean that financing does not contribute to profitability, but because of the high non-performance financing and not yet maximum utilization of assets increases profitability through Islamic finance.Keywords: murabahah, mudharabah, musyarakah, size, return on asset.